Un popolo di colonizzatori? Un itinerario nella storiografia sul colonialismo italiano - Francesco Casales (Laboratoire Italien)
This article aims to enhance to the understanding of the legacy of colonial experience in 20th-century Italian culture and the early 21st century. To this end, it investigates the relationship between the historiography of colonialism and modern Italian history. To what extent has colonial history been considered part of national history? And above all, what are the phases that marked the relationship between these two fields of analysis? In an attempt to contribute to the historicisation of the historiography of Italian colonialism, this article aims to reconstruct the relationship between the narrative of colonial expansion and national history by analysing some classics of historiography on the subject in light of the context in which they were produced.